Blood-Brain Barrier Dysfunction Amplifies the Development of Neuroinflammation: Understanding of Cellular Events in Brain Microvascular Endothelial Cells for Prevention and Treatment of BBB Dysfunction - Takata, Fuyuko; Nakagawa, Shinsuke; Matsumoto, Junichi; Dohgu, Shinya (Frontiers in Cellular Neuroscience, 2021)
Neuroinflammation is involved in the onset or progression of various neurodegenerative diseases. Initiation of neuroinflammation is triggered by endogenous substances (damage-associated molecular patterns) and/or exogenous pathogens. Activation of glial cells (microglia and astrocytes) is widely recognized as a hallmark of neuroinflammation and triggers the release of proinflammatory cytokines, leading to neurotoxicity and neuronal dysfunction. Another feature associated with neuroinflammatory diseases is impairment of the blood-brain barrier (BBB). The BBB, which is composed of brain endothelial cells connected by tight junctions, maintains brain homeostasis and protects neurons. Impairment of this barrier allows trafficking of immune cells or plasma proteins into the brain parenchyma and subsequent inflammatory processes in the brain. Besides neurons, activated glial cells also affect BBB integrity. Therefore, BBB dysfunction can amplify neuroinflammation and act as a key process in the development of neuroinflammation. BBB integrity is determined by the integration of multiple signaling pathways within brain endothelial cells through intercellular communication between brain endothelial cells and brain perivascular cells (pericytes, astrocytes, microglia, and oligodendrocytes). For prevention of BBB disruption, both cellular components, such as signaling molecules in brain endothelial cells, and non-cellular components, such as inflammatory mediators released by perivascular cells, should be considered. Thus, understanding of intracellular signaling pathways that disrupt the BBB can provide novel treatments for neurological diseases associated with neuroinflammation. In this review, we discuss current knowledge on the underlying mechanisms involved in BBB impairment by inflammatory mediators released by perivascular cells.